The politics of development aid : the allocation and delivery of aid from the United States of America to Pakistan : a thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy in Development Studies at Massey University, Palmerston North, New Zealand - Ali, Murad (Massey University, 2012)
This thesis investigates two aspects of the United States of America (USA) foreign aid to Pakistan: allocation and delivery. Regarding the former, the study explores the principal determinants of USA foreign aid to Pakistan during three distinct periods: the Cold War, the post-Cold War of the 1990s and the =war on terror‘ since 2001. In order to have a comprehensive, in-depth and balanced analysis of the primary motivations behind the USA aid disbursement to Pakistan, the study also examines the provision of USA aid to other important USA allies including Egypt, Israel and Turkey. The focus has been to explore to what extent USA foreign aid policies are driven by USA geo-strategic ambitions, and to what extent widely espoused international principles such as poverty reduction as well as democracy and respect for human rights determine USA aid allocations. This research has found that the USA aid regime, both historical as well as contemporary, has largely been motivated and sustained by USA geo-strategic, security and political goals. In the context of USA aid to Pakistan, the thesis finds that the contemporary USA-Pakistan alliance in the =war on terror‘ has striking similarities with the Cold War period. Then, the primary objective of USA aid to Pakistan was anti-communism; now it is anti-terrorism. In relation to the second aspect of the study, the thesis examines the delivery and utilization of USA aid in Pakistan within the 2005 Paris Declaration (PD) framework that contains five interrelated principles aimed at enhancing ownership, alignment, harmonisation, management for development results and mutual accountability between donors and partner countries. Both Pakistan and the USA are signatories to the PD; hence the respective roles of different ministries and departments of the Government of Pakistan (GoP) and the role of Unites States Agency for International Development (USAID) are examined in USA-funded projects. The aim is to investigate to what extent the PD commitments are being implemented in actual practices during the selection, design and execution of development projects. The study has found that there are issues from both the GoP and USAID ends that hinder the actual implementation of the PD commitments. On the part of the former, lack of institutional capacity and corruption are the key challenges. Concerning the latter, USAID still does not delegate authority to GoP institutions to design and implement projects and instead comes up with its own plans and executes these through its international partners working as substitutes for GoP institutions. As a result, almost half of the aid is being consumed by USAID‘s international contractors on the management and administration of USA-funded projects. Furthermore, most aid is being spent on activities which do not address the actual problems of the targeted population. The thesis contributes to the body of knowledge concerning the allocation and delivery of aid from =rich‘ to =poor‘ countries. Its two-fold contribution is, first, it has uncovered the primary determinants of the historical as well as contemporary USA aid provision to Pakistan. Second, it is one of the very few in-depth studies that has looked into the implementation of the PD principles at the country level and has uncovered the constraints responsible for the lack of progress towards achieving the PD partnership commitments in the context of USA aid to Pakistan.
Keywords: American economic assistance; Foreign relations; United States; Pakistan; Development aid; Politics